Physical principles in sensing and signaling: with an introduction to modeling in biology - Endres, Robert G. (Oxford University Press, 2013)
"This textbook is aimed at newcomers in the field of biological physics, especially motivated undergraduate and beginning graduate students with a mathematical and physical background, taking interest in the area of quantitative biology"--